Pattern and drug sensitivity of non-specific bacterial population in tuberculosis patients with multiple drug resistance - A. V. Lavrinenko; I. S. Аzizov; S. I. Kolesnichenko; M. T. Kozhamuratov; N. S. Tabriz; Zh. Mutaykhan (Туберкулез и болезни лёгких, 2019)
The objective: to study the patterns of nonspeciﬁc bacterial population isolated in patients with multiple drug resistant tuberculosis in the city of Karaganda and assess its sensitivity to antimicrobial agents.Subjects and methods. 343 sputum specimens were tested. Microorganisms were identiﬁed using mass spectrometry using the MALDI-TOF method (Microﬂex, BD, Germany). Drug susceptibility was determined by the diﬀusion method in accordance with CLSI recommendations (2012).Results. Bacterial growth was observed in 20.99%. More than ⅔ of isolated microorganisms were resistant to three groups of drugs and more, thus it could be classiﬁed as MDR. S. aureus prevailed in the structure of secondary bacterial population and made 22.22%, of which 12.5% were MRSA. Among gram-negative bacteria, K. pneumoniae – 12.5% and A. baumannii – 11.11% dominated among isolated species. 10% of K. pneumonia strains and from 40 to 70% of A. baumannii were resistant to carbapenems. The secondary bacterial population isolated in pulmonary tuberculosis is represented by nosocomial strains of ESKAPE group, which are typically resistant to modern drugs.